Management of the sale of services through the distance learning system - Vidovic, Aleksandra (Papanda Publishier, 2024)
Education services through distance learning represent a system that allows students easier access to learning, given that the platforms of this system contain all the necessary materials that facilitate, speed up, and improve the distance learning system. The subject of this research is the management of the sale of services through a distance learning system. The goal of this work is to attract students to this way of studying, retain them, and ensure their satisfaction with this kind of learning system, which is a permanent and continuous job. The future behavior is primarily related to the analysis of the current situation, which primarily refers to the quality of the services provided/sold and the satisfaction of users with them. The research method is based on the author’s long-term work and his monitoring of this type of learning. A comparative analysis of the situation then and now is given, and along with the comparative analysis, the most recent research was done based on a survey and interviews of student users of this system, which is a representative sample. The empirical data were analyzed using the statistical program SPSS 22. The recommendation for further work refers to determining what students really want, which essentially represents the successful sale of services. The obtained results refer to the fact that there is no difference in attitudes and degree of satisfaction towards the consumption of this type of learning among different groups of students.